The Relationship Between YouTube Watching Intensity and Language Development in Early Childhood in Pringgowirawan Village - Ahdaniyah, Durrotul Muniroh; Yudha, Rivo Panji (Universitas Muhammadiyah Ponorogo, 2024)
This study aimed to determine the relationship between the intensity of watching YouTube and language development in early childhood (ages 2-5 years). The research employed a quantitative approach with a cross-sectional design and utilized purposive sampling techniques. The study focused on kindergartens in Pringgowirawan Village, which has 5 schools and 190 students. Data collection was carried out using a questionnaire. To analyze the data, the product-moment correlation formula was applied using SPSS.The analysis revealed a significant relationship between the intensity of watching YouTube and language development in early childhood in Pringgowirawan Village, Jember Regency. This was indicated by the SPSS calculation, where the Sig. (2-tailed) value between the intensity of watching YouTube (X) and children's language development (Y) was 0.000 0.05, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). This signifies a significant correlation between the intensity of watching YouTube and children's language development. Since the Pearson correlation coefficient (r) was negative, it indicates that as the intensity of watching YouTube increases, children's language development tends to decrease